Behind the Scenes: The Impact of Bioactive Phenylpropanoids on the Growth Phenotypes of Arabidopsis Lignin Mutants - El Houari, Ilias; Boerjan, Wout; Vanholme, Bartel (Frontiers in Plant Science, 2021)
The phenylpropanoid pathway converts the aromatic amino acid phenylalanine into a wide range of secondary metabolites. Most of the carbon entering the pathway incorporates into the building blocks of lignin, an aromatic polymer providing mechanical strength to plants. Several intermediates in the phenylpropanoid pathway serve as precursors for distinct classes of metabolites that branch out from the core pathway. Untangling this metabolic network in Arabidopsis was largely done using phenylpropanoid pathway mutants, all with different degrees of lignin depletion and associated growth defects. The phenotypic defects of some phenylpropanoid pathway mutants have been attributed to differentially accumulating phenylpropanoids or phenylpropanoid-derived compounds. In this perspectives article, we summarize and discuss the reports describing an altered accumulation of these bioactive molecules as the causal factor for the phenotypes of lignin mutants in Arabidopsis.